PENGARUH PELATIHAN, KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN DI KANTOR PLN (PERSERO) BANDA ACEH - Muhammad Nasir, M. Ridha Siregar (Departemen Manajemen, 2017)
This research aimed to measure the effect of training, compensation and work discipline to job performance of employee in PT. PLN Banda Aceh. The sample used in this research are employee in PT. PLN Banda Aceh which totaled 199 respondents. The methods of this study used a questionnaire as a research instrument. Proportional random sampling was used as sampling technique. As much of 132 questionnaires could be collected. Multiple regression analysis was used as a method of analysis to determine the effect of all variables involved in this research. The results are follows: 1) Training significantly effect to Job Performance of employee in PT. PLN Banda Aceh. 2) Compensation significantly effect to Job Performance of employee in PT. PLN Banda Aceh. 3) Work Discipline significantly effect to Job Performance of employee in PT. PLN Banda Aceh.Keywords: Training, Compensation, Work Discipline, Job Performance.